Inhalation of Hydrogen-rich Gas before Acute Exercise Alleviates Exercise Fatigue: A Randomized Crossover Study - Dong, Gengxin; Wu, Jianxin; Hong, Yinglu; Li, Qian; Liu, Meng; Jiang, Guole; Bao, Dapeng; Manor, Brad; Zhou, Junhong (International Journal of Sports Medicine, 2024)
Hydrogen, as an antioxidant, may have the potential to mitigate fatigue and improve selected oxidative stress markers induced by strenuous exercise. This study focused on a previously unexplored approach involving pre-exercise inhalation of hydrogen-rich gas (HRG). Twenty-four healthy adult men first completed pre-laboratories to determine maximum cycling power (Wmax) and maximum cycling time (Tmax). Then they were subjected to ride Tmax at 80% Wmax and 60–70 rpm on cycle ergometers after inhaled HRG or placebo gas (air) for 60-minute in a double-blind, counterbalanced, randomized, and crossover design. The cycling frequency in the fatigue modeling process and the rating of perceived exertion (RPE) at the beginning and end of the ride were recorded. Before gas inhalation and after fatigue modeling, visual analog scale (VAS) for fatigue and counter-movement jump (CMJ) were tested, and blood samples were obtained. The results showed that compared to a placebo, HRG inhalation induced significant improvement in VAS, RPE, the cycling frequency during the last 30 seconds in the fatigue modeling process, the ability to inhibit hydroxyl radicals, and serum lactate after exercise (p<0.028), but not in CMJ height and glutathione peroxidase activity. The cycling frequency during the last 30 seconds of all other segments in the fatigue modeling process was within the range of 60–70 rpm. In conclusion, HRG inhalation prior to acute exercise can alleviate exercise-induced fatigue, maintain functional performance, and improve hydroxyl radical and lactate levels.
Keywords: oxidative stress; anti-fatigue; hydroxyl radicals; lactate; recovery